Adaptation and resistance of soil prokaryotic communities to drought intensification in old-growth forests and pastures of southwestern Amazonia - Díaz García, Elisa; Boy, Diana; Kilian Salas, Simone; Andrino, Alberto; Sauheitl, Leopold; Poehlein, Anja; Guggenberger, Georg; Horn, Marcus A.; Boy, Jens (Frontiers in Plant Science, 2025)
IntroductionClimate change is predicted to intensify droughts in tropical regions. However, the extent to which drought intensification and the subsequent changes in root exudate (RE) composition reshape soil prokaryotic communities (SPC) remains poorly understood.MethodsWe conducted a 69-day incubation to determine the effects of repeated exposure to severe drought and RE application on the SPC activity and structure in soils under old-growth forests and pastures from southwestern Amazonia. At the beginning of each cycle, microcosms received either artificial RE solution or sterile water; following drying, microcosms were either kept at 30% water holding capacity (WHC) for 18 days, representing the regional WHC in the dry season, or at 5% WHC, simulating severe drought.ResultsDrought intensity and RE availability were the primary drivers of changes in SPC composition and activity. The lowest prokaryotic diversity values were observed in the severe drought treatment with +RE addition for both land-uses. After wetting, +RE microcosms showed higher SPC activity due to the utilization of the supplemented REs. Carbon availability interacted with land-use specific characteristics and partially buffered drought effects on SPC composition in pastures. The SPCs from both land-uses were well-adapted to regional drought conditions. However, repeated severe drought caused significant community shifts towards dominance of a few drought-resistant families.DiscussionIntensifying droughts can reduce prokaryotic diversity and reassemble tropical soil communities toward drought-tolerant taxa, with RE inputs amplifying pos-wetting activity yet exacerbating diversity losses under severe stress. Such changes may compromise ecosystem stability and soil functions under future precipitation regimes.